Culturing oil sands microbes as mixed species communities enhances ex situ model naphthenic acid degradation - Demeter, Marc A.; Lemire, Joe; Yue, Gordon; Ceri, Howard; Turner, Raymond J. (Frontiers in Microbiology, 2015)
Oil sands surface mining for bitumen results in the formation of oil sands process water (OSPW), containing acutely toxic naphthenic acids (NAs). Potential exists for OSPW toxicity to be mitigated by aerobic degradation of the NAs by microorganisms indigenous to the oil sands tailings ponds, the success of which is dependent on the methods used to exploit the metabolisms of the environmental microbial community. Having hypothesized that the xenobiotic tolerant biofilm mode-of-life may represent a feasible way to harness environmental microbes for ex situ treatment of OSPW NAs, we aerobically grew OSPW microbes as single and mixed species biofilm and planktonic cultures under various conditions for the purpose of assaying their ability to tolerate and degrade NAs. The NAs evaluated were a diverse mixture of 8 commercially available model compounds. Confocal microscopy confirmed the ability of mixed and single species OSPW cultures to grow as biofilms in the presence of the NAs evaluated. qPCR enumeration demonstrated that the addition of supplemental nutrients at concentrations of 1 g L-1 resulted in a more numerous population than 0.001 g L-1 supplementation by approximately 1 order of magnitude. GC-FID analysis revealed that mixed species cultures (regardless of the mode of growth) are the most effective at degrading the NAs tested. All constituent NAs evaluated were degraded below detectable limits with the exception of 1-Adamantane carboxylic acid (ACA); subsequent experimentation with ACA as the sole NA also failed to exhibit degradation of this compound. Single species cultures degraded select few NA compounds. The degradation trends highlighted many structure-persistence relationships among the 8 NAs tested, demonstrating the effect of side chain configuration and alkyl branching on compound recalcitrance. Of all the isolates, the Rhodococcus spp. degraded the greatest number of NA compounds, although still less than the mixed species cultures. Overall, these observations lend support to the notion that harnessing a community of microorganisms as opposed to targeted isolates can enhance NA degradation ex situ. Moreover, the variable success caused by NA structure related persistence emphasized the difficulties associated with employing bioremediation to treat complex, undefined mixtures of toxicants such as OSPW NAs.